Learning and teaching about the Shoah: retrospect and prospect. Issue 3 (3rd July 2017) - von Borries, Bodo
ABSTRACT: The "IHRA Education Research Project" and its concluding conference in Lucerne in February 2016 make it necessary to give a summative reflection about normative purposes, empirical results, and pragmatic ways of education about the Shoah. There is some ambivalence in all three fields. "Europeanization" has succeeded, but "universalization" not really. Two necessary (but partly conflicting) main goals are "commemoration of victims" and "prevention of genocides, " implicating conclusions for actual crises like the Syrian civil war and fugitives. In the realm of empirical findings, there are some moral limits of research methods, many illusions about great results can be destroyed, and different "contexts" prove to be absolutely decisive. Therefore, comparisons are very important as well as very difficult, and "normal everyday teaching/learning" has to be distinguished carefully from intervention by "elaborated best-practice teaching." Unavoidably, some of the remarks are given mainly from the special situation and experience of living as a second-generation person in a former perpetrators' society.